Phenotypic spectrum of epidermolysis bullosa associated with α6β4 integrin mutations - Schumann, Hauke; Kiritsi, D.; Pigors, M.; Haußer-Siller, Ingrid; Kohlhase, J.; Peters, J.; Ott, H.; Hyla-Klekot, L.; Gacka, E.; Sieron, A. L.; Valari, M.; Bruckner-Tuderman, L.; et al. (British journal of dermatology, 2013)
Background: Integrin α6β4 is a transmembrane receptor and a key component of the hemidesmosome anchoring complex. It is involved in cell-matrix adhesion and signalling in various tissues. Mutations in the ITGA6 and ITGB4 genes coding for α6β4 integrin compromise dermal-epidermal adhesion and are associated with skin blistering and pyloric atresia (PA), a disorder known as epidermolysis bullosa with PA (EB-PA). Objectives: To elucidate the molecular pathology of skin fragility in eight cases, disclose the underlying ITGA6 and ITGB4 mutations and study genotype-phenotype correlations. Methods: DNA was isolated from ethylenediaminetetraacetic acid-blood samples, and the coding exons and exon-intron boundaries of ITGA6 and ITGB4 were amplified by polymerase chain reaction (PCR), and directly sequenced. Skin samples were submitted to immunofluorescence mapping with antibodies to adhesion proteins of the dermal-epidermal junction. Primary keratinocytes were isolated, and used for RNA and protein extraction, reverse transcription PCR and immunoblotting. Ultrastructural analysis of the skin was performed in one patient. Results: We disclose 10 novel mutations, one in ITGA6 and nine in ITGB4. Skin cleavage was either intraepidermal or junctional. Lethal outcome and PA correlated with loss-of-function mutations in two cases. Solely mild skin involvement was associated with deletion of the C-terminus of β4 integrin. Combinations of missense, nonsense or frameshift mutations caused severe urinary tract involvement in addition to skin fragility in five cases. Conclusions: The present study reveals novel ITGA6 and ITGB4 gene mutations and supports previous reports showing that the phenotype may lack PA and be limited to skin and nail involvement. In four out of six cases of EB-PA, life expectancy was not impaired. A high frequency of urinary tract involvement was found in this study, and represented the main cause of morbidity. Low levels of β4 integrin expression were compatible with hemidesmosomal integrity and a mild skin phenotype.
Gesehen am 26.07.2021